Análisis molecular del gen de celobriohidrolasa II de Colletotrichum lindemuthianum - Morelos Martínez, Ma. Irene (Universidad Michoacana de San Nicolás de Hidalgo, 2020)
Colletotrichum lindemuthianumis a pathogenic ascomycete of Phaseolus vulgaris. This fungus uses an arsenal of enzymes that degrade polysaccharides from the plant cell wall to obtain a carbon source. Cellulose is one of the main components of the plant cell wall and among the enzymes involved in the degradation of this polysaccharide is cellobiohydrolase II (CBHII), which produces cellobiose as the final product. In this work the isolation and molecular-bioinformatic characterization of the cbhII gene of pathogenic races 1472 and non-pathogenic 0 of C. lindemuthianumwas performed. The cbhII gene that codes for a cellobiohydrolase II is 100% identical between both races of the fungus. The species of the genus Colletotrichumhave a single cbhIIgene. CBHII of the species of the genus Colletotrichum show high similarity and identity and contain highly conserved domains; carbohydrate binding module between the residues, linker sequence, catalytic domain with the two aspartate residues involved in catalysis and a tyrosine residue that participates in the configuration of the glucose ring to make it more susceptible to the catalytic reaction. The 3D structure of the CBHII of C. lindemuthianum, showed the ?-barrel topology with seven ?-sheets with the modified TIM barrel topology characteristic of the GH6 family. The overlapping of the CBHII 3D structure of C. lindemuthianumand the crystallized protein of T. reesei, showed a high similarity in the folding and position of the two residues D221and D175at the catalytic site within the barrel tunnel. Both races of C. lindemuthianunhave a basal transcription profile of cbhII, in glucose culture, congruent with catabolic repression and a differential transcription profile of cbhII, in culture with plant cell wall of P. vulgaris. The pathogenic race shows high transcription of cbhII, while in the non-pathogenic race low (celullose) or basal (plant cell wall) levels are observed.

Colletotrichum lindemuthianumes un ascomiceto patógenode Phaseolus vulgaris. Este hongo emplea un arsenal de enzimas que degradan los polisacáridos de la pared celular vegetal para la obtención de una fuente de carbono. La celulosa es uno de los principales componentes de la pared celular vegetal y entre las enzimas que participan en la degradación de este polisacárido estála celobiohidrolasa II (CBHII), que produce celobiosa como producto final. En este trabajo se realizó el aislamiento y caracterización molecular-bioinformática del gen cbhIIde laraza patógena 1472 y de la raza no patógena 0 de C. lindemuthianum.El gencbhII que codifica para una celobiohidrolasa II,es 100% idéntico entre ambas razas del hongoy en las especies del género Colletotrichumse presenta un sologendecbhII. LasCBHII delas especies delgénero Colletotrichum muestran alta similitud e identidad ycontienen dominios muy conservadoscomo elmódulo de unión a carbohidrato entre los residuos, secuencia del linker, dominio catalítico con los dos residuos de aspartato involucrados en la catálisisy unresiduo de tirosina que participa en la configuración del anillo de glucosa para hacerla más susceptible a la reacción catalítica. La estructura 3D de la CBHII de C. lindemuthianum, mostróla topología β-barril con siete β-láminas con la topología del barril TIM modificado característico de la familia GH6. El sobrelapamiento de la estructura 3D de CBHII de C. lindemuthianumy la proteína cristalizada de T. reesei,mostró una alta similitud en el plegamiento y la posición de los dos residuos D221y D175 en el sitio catalíticodentro del túneldel barril.Ambas razas de C. lindemuthianun presentan un perfil de transcripción basal de cbhII, en cultivo con glucosa, congruente con represión catabólicay un perfil de transcripción de cbhIIdiferencialyen cultivo con pared celular vegetal de P. vulgaris. La raza patógena muestra una elevada transcripción de cbhII, mientras que en la raza no patógena se observan niveles bajos (celulosa) o basales (pared celular).
Instituto de Investigaciones Agropecuarias y Forestales. Facultad de Biología. Facultad de Medicina Veterinaria y Zootecnia. Facultad de Agrobiología. Facultad de Químico Farmacobiología. Programa Institucional de Maestría en Ciencias Biológicas
Keywords: info:eu-repo/classification/cti/6; FMVZ-R-M-2020-0336; Fitopatógenos; Bioinformática; Biotecnología; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1971